Physiological attributes of triathletes - Suriano, R.; Bishop, D. (Journal of Science and Medicine in Sport, 2010)
Triathlons of all distances can be considered endurance events and consist of the individual disciplines of swimming, cycling and running which are generally completed in this sequential order. While it is expected that elite triathletes would possess high values for submaximal and maximal measures of aerobic fitness, little is known about how these values compare with those of single-sport endurance athletes. Earlier reviews, conducted in the 1980s, concluded that triathletes possessed lower VO2 max values than other endurance athletes. An update of comparisons is of interest to determine if the physiological capacities of elite triathletes now reflect those of single-sport athletes or whether these physiological capacities are compromised by the requirement to cross-train for three different disciplines. It was found that although differences in the physiological attributes during swimming, cycling and running are evident among triathletes, those who compete at an international level possess VO2 max values that are indicative of success in endurance-based individual sports. Furthermore, various physiological parameters at submaximal workloads have been used to describe the capacities of these athletes. Only a few studies have reported the lactate threshold among triathletes with the majority of studies reporting the ventilatory threshold. Although observed differences among triathletes for both these submaximal measures are complicated by the various methods used to determine them, the reported values for triathletes are similar to those for trained cyclists and runners. Thus, from the limited data available, it appears that triathletes are able to obtain similar physiological values as single-sport athletes despite dividing their training time among three disciplines.